A novel mechanism of toxic injury to the Papez circuit from chemotherapy. Issue 4 (April 2015) - Kwan, Benjamin Yin Ming; Krings, Timo; Bernstein, Mark; Mandell, Daniel M.
Abstract: Toxic effects of chemotherapy delivered via Ommaya reservoir include pericatheter necrosis and toxic leukoencephalopathy. Imaging evidence of toxicity is often asymptomatic, but can be clinically consequential. A young patient, treated for cerebrospinal fluid relapse of acute lymphoblastic leukemia with methotrexate and cytarabine via Ommaya reservoir, presented with acute deterioration of short-term memory. MRI demonstrated extra-ventricular Ommaya catheter position and typical methotrexate-induced changes in the deep white matter, but also signal alteration in the forniceal columns and mammillary bodies, components of the Papez circuit. This case presents a novel mechanism of chemotherapy-induced neurotoxicity associated with extra-ventricular Ommaya catheter position. Specifically, the clinical and imaging findings suggest that extra-ventricular Ommaya catheter position may lead to a direct methotrexate-induced toxicity to the Papez circuit. This provides further clinical evidence of the function of the circuit. The possibility that this patient received a supratherapeutic dose of methotrexate may explain why this presentation with profound memory impairment is not more common. However, this case also provides a potential explanation for patients who receive standard dose chemotherapy via extra-ventricular Ommaya catheter and develop milder memory loss.